Indonesian Children English Development through Home And School Learning - Ratnadewi, Dwijani (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2021)
Learning English as a Foreign Language (EFL) starting at an early age is considered a better alternative than learning EFL at an older age. This study aims to examine the development of children's English capability especially in speaking after they have studied at home with Indonesian parents and at school with Indonesian teachers. This study is a longitudinal case study examining 2 children aged 80 and 52 months. The data were in the form of children's English utterances and were taken within 1-2 year intervals. The data were collected by recording their speech, interviewing both children and parents, and carrying out participant observations during data collection. Data analysis was performed using MLU (mean utterance length); UB (Upper Bound) or the number of morphemes of the longest utterance and Morpheme Acquisition (the types of morphemes acquired). The result is that in general they were able to converse in English, but they had different levels of MLU, UB, and Morpheme acquisition. This difference was ascribed to differences in the EFL intervention and learning experience. The first research subjects learned English with Direct Learning in courses and schools, she got her English in no time and her MLU was moderate. The second research subject experienced learning English from a very early age at home with his parents, his MLU was high.